Initial findings on student progress and satisfaction in a new model of hyperflexible online delivery for university students - Colin Beer; Kate Ames; Noal Atkinson; Damien Clark; Peter Hosie (Journal of Global Education and Research, 2024)
University degrees are usually delivered in defined sessions —by term, semester, or in week-based blocks— whereby students are required to complete their studies by the due date. Term or session-based schedules that require students to complete the study within set timeframes are, however, potentially restrictive. Temporal challenges associated with work and life can impede progress and add to the specific problem of student attrition in online learning. As universities seek to deliver innovative options for their students, increased attention is being paid to alternate models of delivery. This paper reports on the development of a hyperflexible online Master of Business Administration (MBA) course by a regional university in Australia, which has grown to more than 1,000 students since its launch in 2017. Delivered entirely online, the degree was specifically designed to address an inequity; MBA programs are traditionally expensive, and in Australia, the requirement for students to travel to attend residential schools and examinations adds significant cost to already expensive tuition fees. This paper analyzed enrollment data, course analytics over a two-year period, and student surveys conducted at the end of the second year of delivery (n = 98) to evaluate the development and implementation of the course as a hyperflexible course whereby students have almost complete control over their study at the postgraduate tertiary level. Results highlight the potential for the model to enable student success through flexibility.